A revision of the bee genus Augochlora Smith (Hymenoptera; Apoidea) in Southern South America - Lepeco, Anderson; Gonçalves, Rodrigo Barbosa (Zootaxa, 2020)
Even after more than 250 years of taxonomic research on bees, there are still many gaps in the knowledge about their identity, classification and distribution patterns. Regarding the New World tribe Augochlorini, many efforts have been made in the last years to describe and organize its diversity. Within the tribe, Augochlora Smith has the widest distribution range, as these bees occur from Argentina to Southern Canada, including Caribbean islands. The genus comprises 124 described species in two extant subgenera, and, to date, two partial revisions are available, accounting for central Argentina and Uruguay and for northeastern Brazil. In the present study we review the Augochlora species occurring in Argentina, Paraguay, Uruguay and the southern Brazilian states of Paraná, Rio Grande do Sul, and Santa Catarina. Specimens from other Brazilian states and South American countries were also examined to help with species circumscription. We found 27 species in the studied area, including nine new species (Augochlora atlantica sp. nov., A. australis sp. nov., A. genalis sp. nov., A. helena sp. nov., A. hestia sp. nov., A. hirsuta sp. nov., A. laevicarinata sp. nov., A. mendax sp. nov., and A. scabrata sp. nov.) and the remaining redescribed when necessary. A key for the species occurring in the studied area is provided. Five new synonymies are proposed and the lectotypes of Augochlora francisca and Halictus esox are presently designated. The geographic distribution of most studied species is associated with the Atlantic biome in many ways.